Pentoxifylline Inhibits Hypoxia-induced Upregulation of Tumor Cell Tissue Factor and Vascular Endothelial Growth Factor - Amirkhosravi, Ali; Meyer, Todd; Warnes, Gary; Amaya, Mildred; Malik, Zaiba; Biggerstaff, John P.; Siddiqui, Farooq A.; Sherman, Paul; Francis, John L. (Thrombosis and Haemostasis, 1998)
Tissue factor (TF), the membrane glycoprotein that initiates blood coagulation, is constitutively expressed by many tumor cells and is implicated in peri-tumor fibrin deposition and hypercoagulability in cancer. Upregulation of tumor TF correlates with enhanced metastatic potential. Furthermore, TF has been colocalized with VEGF in breast cancer, specially at sites of early angiogenesis. There are no data on the effect of hypoxia on tumor cell TF expression. Since hypoxia is known to stimulate VEGF production, we studied whether this also induces tumor cell TF expression. Confluent monolayers of A375 melanoma, MCF-7 breast carcinoma and A549 lung carcinoma were cultured in either 95% air, 5% CO2 (normoxic) or 95% N2, 5% CO2 (hypoxic; 25-30 mmHg) for 24 h. Procoagulant activity (PCA) was measured by amidolytic and clotting assays, surface TF antigen by flow cytometry, early apoptosis by annexin V binding and VEGF levels in culture supernatants by ELISA. Hypoxia significantly increased tumor cell PCA in all three cell lines tested and TF antigen on A375 cells was increased four-fold (P <0.05). Pentoxifylline (PTX), a methylxanthine derivative, significantly inhibited the hypoxia-induced increase in PCA as well as VEGF release in all three cell lines tested. In A375 cells, PTX significantly inhibited TF antigen expression by both normoxic and hypoxic cells. Hypoxia induced a slight (5%) but not significant, increase in early apoptosis. Intravenous injection of hypoxic A375 cells into nude rats produced more pronounced thrombocytopenia (n = 5, P <0.01) and more lung metastases (n = 3, P <0.05) compared to normoxic cells. We conclude that hypoxia increases TF expression by malignant cells which enhances tumor cell-platelet binding and hematogenous metastasis. Hypoxia-induced upregulation of TF appears to parallel that of VEGF, although the mechanism remains unclear.